EXPERIMENTAL DETERMINATION OF STIFFNESS WINCH RUNNER AND HER ATTESTATION OF THE TENSION EXAMINATION ACCORDING TO ČSN 42 0305 (Perner's Contacts, 2011)
This contribution describes the proposal modelling arrangement exploited to experimental assesment stiffness winch runner at uplift empty weight through cable winch. In due is according to theoretic thinking about time behaviour stroke empty weight (funicular tackle, install on trolley crane) experimentally identified stiffness rope and the is juxtaposition with stiffness ropes, which was amenability tension test for shredder.
Keywords: stiffness winch runner; lifting device; trolley crane